THE EFFECT OF SOCIAL CLASS ON CRIME: THE CASE OF SIVAS CUMHURIYET UNIVERSITY STUDENTS - BİNDİK, Sabuha (SSD Journal, 2021)
The relationship between social class and crime has been one of the important issues in criminology. Although this issue has been studied much in the West, the number of studies examining the relationship between social class and crime in Turkey is quite limited. The purpose of this study is to discover whether so”cial class has an effect on crime or not, if it has an effect, to explore what the direction of the relationship is (positive or negative). In this study, the relationship between social class and crime has been examined by using the data obtained from the students at Sivas Cumhuriyet University in 2020 (n= 2,514).The study was based on the hypothesis that the lower social class, the general trend in Western literature, committed more crimes. But the findings of the study have questioned the hypothesis that the lower social class is more criminal. According to the results of the study, as the social class levels of the students involved in the study increase, they are also more likely to engage in criminal behavior. In parallel with the limited number of studies in Turkey, the findings of the relevant research show that the impact of social class on crime is significant but weak.